Hourly Sulfur Dioxide Observations Over North America: First Retrieval Results From TEMPO - Can Li; Nickolay A. Krotkov; Joanna Joiner; Simon Carn; Vitali Fioletov; Chris McLinden; Debora Griffin; Xiong Liu; Heesung Chong (Geophysical Research Letters, 2025)
Abstract We present the first sulfur dioxide (SO2) retrievals from Tropospheric Emissions: Monitoring of Pollution (TEMPO), the first geostationary atmospheric composition sensor to cover North America, along with some potential applications of TEMPO SO2 data. We show that high resolution (∼10 km2) TEMPO measurements can be used to produce good quality SO2 retrievals with relatively small noise and biases. We demonstrate that hourly TEMPO data are useful for monitoring volcanic hazards, by providing frequent updates on the plume location and additional information on the plume height or winds. With the large number of measurements from TEMPO, it is also feasible to monitor diurnal changes in SO2 for relatively large sources such as the Cantarell oil field. We also show that high‐cadence TEMPO measurements allow estimates of SO2 degassing from Popocatépetl volcano on sub‐daily timescales. Overall, our results suggest that TEMPO can significantly enhance space‐based SO2 detection and monitoring over North America.